PENGARUH MEDIA PEMBELAJARAN POHON BERMAJAS TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Indonesian language learning in elementary schools, particularly on figurative language (majas), still faces several challenges, including students’ low understanding of various types of figurative language due to abstract learning methods and limited use of engaging instructional media. This condition has an impact on students’ low learning outcomes. This study aims to examine the effect of using the figurative tree media (pohon bermajas) on elementary school students’ Indonesian language learning outcomes in figurative language material. The study employed a quantitative approach with a pre-experimental one-group pretest–posttest design. The research subjects were sixth-grade students of SD Negeri Klampis 02. Data were collected through learning outcome tests in the form of pretests and posttests, while data analysis was conducted using a paired sample t-test at a significance level of 0.05. The results indicated that the mean posttest score was higher than the mean pretest score. Statistical analysis showed that the calculated t value exceeded the critical t value and the significance value was less than 0.05, leading to the rejection of the null hypothesis. Therefore, it can be concluded that the use of figurative tree media has a significant effect on improving elementary school students’ Indonesian language learning outcomes in figurative language material. The figurative tree media effectively helps students understand abstract concepts more concretely, increases active participation, and enhances learning motivation.